2021
DOI: 10.21107/dinar.v8i1.10581
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Women In Improving The Family Economy

Abstract: The purpose of this study was to determine the role of women in improving the family economy, especially women who work as shallot retail workers. This study uses a qualitative descriptive method, namely formulating a data obtained from words or sentences separated according to the intended category to obtain conclusions. The results of this study conclude that women have a role in helping the family economy. The main reasons why women have to work outside rather than domestic work are economic reasons and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…This leadership also does not deprive women of their rights in various aspects, including the right to own private property and manage it even without the husband's consent. Some previous studies (Mubarok, 2017;Aini, 2019;Hasan et al, 2019;Marwanti & Astuti, 2012;Zuhri et al, 2019;Zunaidi & Maghfiroh, 2021) also showed that women in poor groups also have a role in supporting their family's economic needs, where the Grameen Bank concept is considered suitable to be applied but requires more attention to operational risks. Uddin (2014), Ranabahu & Wickramasinghe (2022) and Indah & Hakim (2023) suggest that the success of Grameen Bank in empowering women is strongly influenced by leadership roles that exhibit vision, commitment, honesty, and create a healthy environment for program implementation within each empowerment group.…”
Section: Introductionmentioning
confidence: 99%
“…This leadership also does not deprive women of their rights in various aspects, including the right to own private property and manage it even without the husband's consent. Some previous studies (Mubarok, 2017;Aini, 2019;Hasan et al, 2019;Marwanti & Astuti, 2012;Zuhri et al, 2019;Zunaidi & Maghfiroh, 2021) also showed that women in poor groups also have a role in supporting their family's economic needs, where the Grameen Bank concept is considered suitable to be applied but requires more attention to operational risks. Uddin (2014), Ranabahu & Wickramasinghe (2022) and Indah & Hakim (2023) suggest that the success of Grameen Bank in empowering women is strongly influenced by leadership roles that exhibit vision, commitment, honesty, and create a healthy environment for program implementation within each empowerment group.…”
Section: Introductionmentioning
confidence: 99%
“…With the women emancipation, many housewives also become careerwomen, both to help their families and financially because of their desire to work (Gui, 2020). Some reasons mothers work in most families are to improve family welfare, the desire to develop, and a sense of responsibility in maintaining, growing, and developing members of families with different types of needs (Moore, 2013;Zunaidi & Maghfiroh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that women's participation in the public world can further enhance the development of family welfare, community prosperity, and development success (Manembu, 2015). Where the involvement of women in social and economic activities in the public sphere is able to make a major contribution to changes in their social position in the household (Zunaidi & Maghfiroh, 2021). The increasing prices of basic commodities, education and other household needs have forced housewives to rack their brains to divide or allocate their husband's money to meet their household needs (Marsha & Nurpatria, 2018).…”
Section: Introductionmentioning
confidence: 99%